Innovative female-led startups. do women in business underperform? - Paola Demartini (Administrative Sciences, 2018)
The spur of innovative startups has provided an unprecedented opportunity for female entrepreneurship. However, the mainstream literature on startups has elaborated a gender performance gap hypothesis. Considering the speed of technological, social, and cultural changes that have taken place in this millennium, we wonder if this gap can still be found today, with particular reference to new technology-based ventures. A financial analysis has been conducted on a sample of innovative Italian startups, and the following variables have been used to assess the company's success: (i) size, (ii) profitability, (iii) efficiency, (iv) financial structure, and (v) financial management. Our results reveal that as far as financial performance is concerned, innovative female-led startups do not lag behind male ones in terms of dimension, company profitability, efficiency, and financial management. However, findings confirmed, even for our sample, that female businesses raise, on average, a lower amount of financial resources in comparison to men.
Keywords: 350; Innovative female startups; underperformance hypothesis; gender gap; high tech female entrepreneur